Chronotype is associated with psychological well-being depending on the composition of the study sample. (August 2020) - Dimitrov, Annika; Veer, Ilya M; Kleeblatt, Julia; Seyfarth, Florian; Roenneberg, Till; Ising, Marcus; Uhr, Manfred; Keck, Martin E; Kramer, Achim; Berger, Maximilian; von Koch, Lara; Walter, Henrik; et al.
Past studies examining the effect of chronotype and social jetlag on psychological well-being have been inconsistent so far. Here, we recruited participants from the general population and enquired about their natural sleeping behavior, sleep quality, depressive symptoms, and perceived stress. Partial correlations were computed between sleep variables and indicators of psychological well-being, controlling for age and sex. Less sleep during work days was found a good indicator for impairments in psychological well-being. In exploratory follow-up analyses, the same correlations were calculated within groups of early, intermediate, and late chronotype. We observed that the composition of the sample in terms of chronotype influenced whether associations between sleep variables and psychological well-being could be observed, a finding that is advised to be taken into account in future studies.